PENGARUH KEPEMIMPINAN, KOMPENSASI, LINGKUNGAN KERJA DAN WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan PT. Kereta Api Indonesia (Persero) Daerah Operasi (DAOP) IV Semarang) - Nuraningsih, Cahya Indah; Harries Arizonia Ismail (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2024)
This research examines the impact of leadership, salary, work environment, and work-life balance on worker performance at PT. Indonesian Railways (Persero) Operational Area 4 Semarang. By using a quantitative approach and a questionnaire survey of 145 employee respondents, the research concluded that each variable had a significant effect on employee performance. All research measuring instruments were declared valid and reliable based on the results of validity and reliability tests. Multiple linear regression research shows that leadership, salary, working conditions, and work-life balance have a positive effect on employee performance. These findings provide important information for improving management strategies and human resource development in companies.